Mutant SOD1 aggregates formed in vitro and in cultured cells are polymorphic and differ from those arising in the CNS. Issue 1 (23rd November 2022) - Nordström, Ulrika; Lang, Lisa; Ekhtiari Bidhendi, Elaheh; Zetterström, Per; Oliveberg, Mikael; Danielsson, Jens; Andersen, Peter M.; Marklund, Stefan L.
Abstract: Mutations in the human Superoxide dismutase 1 ( hSOD1 ) gene are well‐established cause of the motor neuron disease ALS. Patients and transgenic (Tg) ALS model mice carrying mutant variants develop hSOD1 aggregates in the CNS. We have identified two hSOD1 aggregate strains, which both transmit spreading template‐directed aggregation and premature fatal paralysis when inoculated into adult transgenic mice. This prion‐like spread of aggregation could be a primary disease mechanism in SOD1‐induced ALS. Human SOD1 aggregation has been studied extensively both in cultured cells and under various conditions in vitro. To determine how the structure of aggregates formed in these model systems related to disease‐associated aggregates in the CNS, we used a binary epitope‐mapping assay to examine aggregates of hSOD1 variants G93A, G85R, A4V, D90A, and G127X formed in vitro, in four different cell lines and in the CNS of Tg mice. We found considerable variability between replicate sets of in vitro‐generated aggregates. In contrast, there was a high similarity between replicates of a given hSOD1 mutant in a given cell line, but pronounced variations between different hSOD1 mutants and different cell lines in both structures and amounts of aggregates formed. The aggregates formed in vitro or in cultured cells did not replicate the aggregate strains that arise in the CNS. Our findings suggest that the distinct aggregate morphologies in the CNS could result from a micro‐environment with stringent quality control combined with second‐order selection by spreading ability. Explorations of pathogenesis and development of therapeutics should be conducted in models that replicate aggregate structures forming in the CNS. Abstract : In this issue Nordström et al. show that ALS associated superoxide dismutase 1 (SOD1) aggregates generated in vitro and in cell culture models are deviant from the aggregations that arise in the CNS of Tg mouse models of ALS. The study suggests that development of different strains of SOD1 aggregation in the CNS may depend on different disease associated variations in the amino acid sequence, combined with a selection pressure imposed by cell type specific micro‐environments, proteostasis control and prion‐like spread competence.